2016
DOI: 10.1016/j.pnpbp.2015.08.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of striatal dopamine depletion on striatal and cortical glutamate: A mini-review

Abstract: Understanding the interplay between the neurotransmitters dopamine and glutamate in the striatum has become the highlight of several theories of neuropsychiatric illnesses, such as schizophrenia. Using in vivo brain imaging in humans, alterations in dopamine and glutamate concentrations have been observed in several neuropsychiatric disorders. However, it is unclear a priori how alterations in striatal dopamine should modulate glutamate concentrations in the basal ganglia. In this selective mini-review, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 60 publications
6
14
0
Order By: Relevance
“…In the ORT performance measure, a preference for the novel object is considered to be an index of consolidated memory for the familiar object (35). Overall, object investigation did not differ between anti-GAPDH-treated mice and untreated control mice (F [1,12] 5 2.609, P 5 0.1322). However, the discrimination index (measuring memory retention) was worse in anti-GAPDH-treated mice compared with untreated controls (F [1,11] In the EPM apparatus, only anti-GAPDHtreated mice showed a reduced latency to immobility (F [1,11] 5 5,150, P 5 0.0444) ( Figure 4B) in addition to an increased frequency of, and trend toward, a higher duration of this behavior in the open arms of the maze, suggesting that emotionality was increased in the anti-GAPDH-treated mice (F [2,24] 5 3.636, P 5 0.0417 for frequency; F [2,24] 5 2.872, P 5 0.0762 for duration).…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…In the ORT performance measure, a preference for the novel object is considered to be an index of consolidated memory for the familiar object (35). Overall, object investigation did not differ between anti-GAPDH-treated mice and untreated control mice (F [1,12] 5 2.609, P 5 0.1322). However, the discrimination index (measuring memory retention) was worse in anti-GAPDH-treated mice compared with untreated controls (F [1,11] In the EPM apparatus, only anti-GAPDHtreated mice showed a reduced latency to immobility (F [1,11] 5 5,150, P 5 0.0444) ( Figure 4B) in addition to an increased frequency of, and trend toward, a higher duration of this behavior in the open arms of the maze, suggesting that emotionality was increased in the anti-GAPDH-treated mice (F [2,24] 5 3.636, P 5 0.0417 for frequency; F [2,24] 5 2.872, P 5 0.0762 for duration).…”
Section: Resultsmentioning
confidence: 93%
“…However, the discrimination index (measuring memory retention) was worse in anti-GAPDH-treated mice compared with untreated controls (F [1,11] In the EPM apparatus, only anti-GAPDHtreated mice showed a reduced latency to immobility (F [1,11] 5 5,150, P 5 0.0444) ( Figure 4B) in addition to an increased frequency of, and trend toward, a higher duration of this behavior in the open arms of the maze, suggesting that emotionality was increased in the anti-GAPDH-treated mice (F [2,24] 5 3.636, P 5 0.0417 for frequency; F [2,24] 5 2.872, P 5 0.0762 for duration). Anti-GAPDH-treated mice also tended to show a reduced latency to the stretched-attend posture (F [1,12] 5 3.850, P 5 0.0733), a behavior that is indicative of an anxiety-like profile.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In turn, striatal glutamate levels were found to be negatively correlated with dorsal caudate volumes in these patients [Plitman et al, ]. Given the potential interactions between striatal DA and glutamate [Caravaggio et al, ; Stone et al, ], it can be inferred that the dopaminergic changes observed in schizophrenia may also be related changes in brain morphology. However, without direct evidence this remains merely conjuncture.…”
Section: Discussionmentioning
confidence: 99%
“…That idea that NAc dopamine maintains and controls our normal drives relating to pleasure is well established [172][173][174]. In fact, dopamine is thought of as the anti-stress and pleasure molecule [175][176][177][178][179]. Synaptic release of dopamine stimulates some receptors (D1-D5), leading to increased feelings of well-being and stress reduction [180][181][182].…”
Section: Dopamine Agonist Therapy: Changing the Recovery Landscapementioning
confidence: 99%